Description of Main Innovative and Alternative Methodologies for Mathematical Learning of Written Algorithms in Primary Education - Canto López, María del Carmen; Manchado Porras, Malena; Piñero Charlo, José Carlos; Mera Cantillo, Carlos; Delgado Casas, Cándida; Aragón Mendizábal, Estíbaliz; García Sedeño, Manuel Antonio (Frontiers in Psychology, 2022)
The traditional way of teaching mathematics generates significant learning difficulties in students that are reflected in their academic performance. This has revealed the need for a methodological change. In recent years, the number of teachers interested in finding innovative, flexible, and understandable methodologies has increased. Therefore, research on mathematics teaching has also increased, seeking to offer quality and evidence-based methodological alternatives. In this paper, we intend to provide an overview of some innovative mathematics teaching strategies that have emerged in recent years in different countries, and that show direct practical effects in the classrooms. These methodologies focus on elements such as number sense and mental arithmetic, avoiding memoristic and mechanical procedures. Thus, they also promote the improvement of affective factors such as motivation or attitude towards mathematics, which have an important influence on mathematical performance. This text presents the main characteristics of two international methods: the Holland algorithms and the American algorithms; and three national initiatives: the Other Algorithms for Arithmetic Operations (OAOA) method, the Singapore method and the Open method based on numbers (ABN) method. The core elements of each initiative, some of which are common, have been highlighted, as well as examples of mathematical strategies applied in the classroom. Data show that the traditional methodology followed in several countries has some limitations in preparing students for mathematics. Moreover, alternative methodologies are a necessary driver for the improvement of mathematical performance both inside and outside the classroom, and also for the technological and economic development of countries.